THU0648 Use of outpatient rheumatologic health care services before and after switch from originator to biosimilar infliximab. (15th June 2017) - Glintborg, B; Sørensen, J; Hetland, ML
Abstract : Background: According to Danish national guidelines issued in 2015, pts (pts) with inflammatory rheumatic diseases in routine care treatment with originator infliximab (INX) must switch to the cheaper biosimilar infliximab (CT-P13). This switch was done for economic reasons (CT-P13 64% cheaper than INX). Since any treatment change potentially induces additional guidance of pts and use of hospital services, it is relevant to investigate whether the switch affected use of hospital resources. Objectives: To study difference in rates of outpatient activities and services provided 6 months before vs after the switch to CT-P13 for pts treated at rheumatologic departments which provide infliximab treatment. Methods: The switch population and switch dates were identified in the Danish quality registry, DANBIO (1). Vital status was validated in the Central Person Registry. The Danish National Patient Registry (NPR) provided information regarding outpatient contacts and services. The use of 16 types of services relevant to the rheumatologic specialty was identified and included outpatient visits, infliximab infusion, nurse counselling, phone consultation, and rheumatologic ultrasound. Number of days with these services was counted. Services performed on the switch date were analyzed separately. Thus, for each patient the following rates were calculated 6 months before and after the switch: 1) days with at least one outpatient service provided, and 2) number of services provided. In addition, the weekly rate of days with services was calculated. Only pts who were alive and could be followed in the NPR for 6 full months after the switch were included. Paired t-tests were used to compare rates before and after switch. A graphical interrupted time series analysis was conducted for weekly number of services provided. Results: Among 802 pts identified, 769 had available NPR outpatient data from hospital departments of rheumatology. The 769 pts had 1484 outpatient treatment contacts at the included rheumatology departments with a total of 9243 days with services provided (including 693 on the switch date). The mean rate of days with services provided was 5.4 before the switch and 5.7 after switch (p=0.0003). The weekly rate of days with services showed no obvious differences before and after the switch but had a clear 8-week pattern (corresponding to the average infusion interval) (Figure). The total number of services provided was 19, 752 (2, 019 of these on the switch date). There were significant increases in the rates before vs after switch for 6 of the 16 service categories, although the mean rates were small: telephone consultations (mean rate 1.0 before vs. 1.2 after), patient guidance (0.5 vs. 0.4), intravenous medication (0.0 vs. 0.1), clinical controls (2.1 vs. 2.3) and clinical investigations (0.3 vs. 0.5), whereas the rate of infliximab treatment decreased (3.1 vs 3.0) (all p<0.05, insignificant results not shown). Conclusions: This analysis showed that there were only small differences in the rates of days with outpatient services and rates of services 6 months before and after the switch from original to biosimilar infliximab. Thus, it is unlikely that the switch is associated with substantially higher cost of health care resources. References: Glintborg et al. Arthritis Rheumatol. 2016; 68 (suppl 10). Disclosure of Interest: B. Glintborg Grant/research support from: Abbvie, J. Sørensen Grant/research support from: Abbvie, M. Hetland Grant/research support from: Orion, BMS, AbbVie, Biogen, Pfizer, MSD